MEWUJUDKAN GENERASI MUDA YANG MAMPU BERDAYA SAING DENGAN MELIBATKAN PERGURUAN TINGGI - Siti Nurhaliza Amelia Putri Pratami; Aprilia Rizki Pradani; Eka Nurfaidah (Cahaya Ilmu Bangsa, 2025)
Youth is one of the most important capital for the Indonesian nation in the future nation building, meaning that it is important to have the role of youth in national development. To become a developed nation and be able to compete in international arena, the role of youth as the nation's successors is a requirement mandatory that must be fulfilled. The relationship between education and national, even international, competitiveness. Indonesia's national competitiveness has fluctuated over the years. By examining various data, is there an educational factor that determines the nation's competitive position? Through the analysis of various documents and articles, including journals and books, it becomes evident that education is one of the key pillars of a nation's competitiveness. The author gathered material through library research and employed descriptive analysis. The author's findings indicate that education is a critical endeavor for a nation to enhance the quality of its human resources. Therefore, improving the quality and equity of education is essential because it is through education that individuals can become highly competitive and quality-driven individuals.